2017
DOI: 10.1002/chem.201703680
|View full text |Cite
|
Sign up to set email alerts
|

Mild Decarboxylative C−H Alkylation: Computational Insights for Solvent‐Robust Ruthenium(II) Domino Manifold

Abstract: Computational studies on decarboxylative C-H alkenylations provided key insights into the solvent-robust nature of C-H activation/decarboxylation domino reactions. These properties were exploited for ruthenium(II)-catalyzed C-H alkylations by a decarboxylative process with ample scope under copper-free and silver-free reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 84 publications
2
36
0
4
Order By: Relevance
“…Ther obust ruthenium(II) carboxylate manifold was fully tolerant of air and H 2 O, with optimal results obtained in as olvent mixture of tert-amyl alcohol and H 2 Ow ith sodium pivalate as the additive (entries [5][6][7][8][9][10]. Control experiments reflected the outstanding performance of the ruthenium(II) carboxylates [11] (entries [8][9][10][11][12][13][14][15][16][17][18][19], while typical iridium, cobalt, and palladium catalysts fell short in delivering the desired product 3aa (entries [11][12][13][14][15]. …”
mentioning
confidence: 99%
“…Ther obust ruthenium(II) carboxylate manifold was fully tolerant of air and H 2 O, with optimal results obtained in as olvent mixture of tert-amyl alcohol and H 2 Ow ith sodium pivalate as the additive (entries [5][6][7][8][9][10]. Control experiments reflected the outstanding performance of the ruthenium(II) carboxylates [11] (entries [8][9][10][11][12][13][14][15][16][17][18][19], while typical iridium, cobalt, and palladium catalysts fell short in delivering the desired product 3aa (entries [11][12][13][14][15]. …”
mentioning
confidence: 99%
“…During our mechanistic studies on kinetics of ruthenium‐catalyzed C−H activation, we observed the incorporation of deuterium into alkenes with unique selectivity features . Our investigations indicated that this profile was due to an unprecedented alkene deuteration, unexpectedly occurring prior to the C−H activation event.…”
Section: Methodsmentioning
confidence: 82%
“…The practical utility and key mechanistic implications of the C−H activation‐based HIE was next applied to the position‐ and chemo‐selective preparation of biorelevant, naturally occurring compounds. Hence, our HIE approach proved applicable towards the preparation of phthalides of type [D] 3 ‐ 5 b (Scheme a) – key structural motifs in various natural products – from substrate [D 2 ]‐ 4 without notable primary kinetic isotope effect (KIE) in the ruthenium oxidase, catalysis manifold (Scheme b).…”
Section: Methodsmentioning
confidence: 99%
“…[75a] Es wurde gezeigt, dass die elektronischen Eigenschaften der Ausgangsbenzoesäuren das Ergebnis der Reaktion nur geringfügig beeinflussten und dass meta-substituierte Benzoesäuren überwiegend in der am wenigsten gehinderten Position alkyliert wurden. [76] Kurz darauf folgten Berichte über eine rhodium-/ kupfercokatalysierte,c arboxydirigierte ortho-Alkylierung mit konjugierten Ketonen, die in situ durch Dehydrierung der entsprechenden Ketone erzeugt wurden, [75b] sowie über eine rutheniumkatalysierte Oxidation/Alkylierung mit Allylalkoholen.…”
Section: Alkylierung Aromatischer Carbonsäuren Mit Alkenenunclassified